Novel Small Molecules Capable of Blocking mtRAS-Signaling Pathway - Kim, Namkyoung; Shin, Injae; Kim, Younghoon; Jeon, Eunhye; Lee, Jiwon; Lee, Chaeyoung; Nam, Yunju; Lee, Sumin; Ju, Eunhye; Kim, Chan; Son, Woolim; Ryu, SeongShick; et al. (Frontiers in Oncology, 2021)
RAS mutants are involved in approximately 30% of all human cancers and have been regarded as undruggable targets owing to relatively smooth protein surface and obscure binding pockets. In our previous study, we have demonstrated that GNF-7, a multi-targeted kinase inhibitor, possesses potent anti-proliferative activity against Ba/F3 cells transformed with NRAS-G12D. Based on our further analysis using Ba/F3 cells transformed with mtRAS, we discovered a series of pyrimido[4,5-d]pyrimidin-2-one analogues as mtRAS-signaling pathway blockers. In addition, our efforts expanded the assessment to cancer cells with mtRAS, which revealed that these substances are also capable of strongly suppressing the proliferation of various cancer cells harboring KRAS-G12D (AsPC-1), KRAS-G12V (SW480, DU-145), KRAS-G12C (H358), KRAS-G13D (MDA-MB-231), KRAS-Q61L (HT-29), and NRAS-Q61L (OCI-AML3). We herein report novel and potent mtRAS-signaling pathway blockers, SIJ1795 and SIJ1772, possessing 2 to 10-fold increased anti-proliferative activities compared to those of GNF-7 on cancer cells harboring mtRAS as well as on Ba/F3 cells transformed with mtRAS. Both SIJ1795 and SIJ1772 attenuate phosphorylation of RAS downstream molecules (AKT and MEK) and induce apoptosis and G0/G1 cell cycle arrest on cancer cells with mtRAS. Moreover, both substances substantially suppress the migration, invasion, and colony formation of cancer cells harbouring mtRAS. Taken together, this study led us to identification of SIJ1795 and SIJ1772 capable of strongly inhibiting mtRAS-signaling pathway on cancer cells harboring mtRAS.